Characteristics and Dynamic Process Modeling of the Rainfall-Induced Landslide on August 21, 2020 in Hanyuan County, China - Yang, Weibin; Wang, Fulei; Tie, Yongbo; Wang, Dongpo; Ouyang, Chaojun (Frontiers in Earth Science, 2021)
On August 21, 2020, a landslide occurred in Zhonghai village of Hanyuan County, Sichuan Province, China. The landslide is triggered by two successive rounds of heavy rainfall. This landslide can be clearly divided into an initial landslide and a main landslide. The main landslide is activated by the intense impact and overloading of the initial landslide. The depth-integrated continuum method is adopted to simulate the dynamic process. Due to the complicated failure process, it is found that there is no proper unified parameters in Coulomb model which could well reproduce the two successive landslides. It implies that the dynamic process of landslides is highly associated with the characteristics of sliding bodies. Here, an implement of variable frictional coefficients for different parts is proposed and the parameters are calibrated. It is demonstrated that results from numerical modeling match well with the field investigation. The complicated landslides in two different stage can both be efficiently revealed by depth-integrated continuum modeling.